2020
DOI: 10.1002/cam4.3533
|View full text |Cite
|
Sign up to set email alerts
|

Survival trends and prognostic factors in patients with solitary plasmacytoma of bone: A population‐based study

Abstract: Solitary plasmacytoma of bone (SPB) is a single, isolated plasmacytoma originated from the bone. The survival trends of patients with SPB in recent years remain unknown. And the prognostic system of SPB may also need to be refined. The 18 Surveillance, Epidemiology, and End Results (SEER) databases of the National Cancer Institute in the United States were used to extract data for this study. The third edition of the International Classification of Disease for Oncology (ICD‐O‐3) code 9731 was used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…The most common presenting symptom of an SBP is bone pain [ 11 - 13 ]. Depending on its location, it may also present with signs of compression neuropathy and pathologic fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common presenting symptom of an SBP is bone pain [ 11 - 13 ]. Depending on its location, it may also present with signs of compression neuropathy and pathologic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown that a post-treatment protein level >0.5 g/dL is associated with a negative prognosis. It should also be noted that the presence and quantity of serum monoclonal proteins at diagnosis yields no prognostic information [ 13 , 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Solitary bone plasmacytoma (SBP) is a kind of primary malignant tumors due to monoclonal plasma cell infiltrate and lesions, approximately 5% of all cases of plasma cell disorders (The incidence rates (IRs) is 0.34 per 100,000 person-years [1] ) are SPB, which comprises 70% of all solitary plasmacytoma (SP) and occurs primarily in the red marrow-containing bones of the axial skeleton, the most common site is the thoracic spine, and the cervical spine is rare spine [2] , [3] , [4] , [5] , [6] . The most common symptom is pain and can also show compression of the spinal cord or nerve roots.…”
Section: Introductionmentioning
confidence: 99%